English Learning Needs of Non-English Major Students of Higher Education - *, Jamilah (Sebelas Maret University, 2016)
This study was a part of a program development and aimed at finding out the English learning needs of non-English major students of Yogyakarta State University. The study was a triangulated survey techniqueemploying questionnaires as the main instrument to collect the data and was completed with interview,observation, and document study. The subject of the study included students, English teachers, and managersat all levels, sampled randomly. Data from the questionnaires were analyzed descriptively and were validatedwith the data from the other techniques.The findings show that students find English skill very important fortheir life and their study, and they need to learn it in order to achieve various goals, such as to communicatewith foreigners, to read books and articles of their majors, to get high score of TOEFL, to be able to useinternet better, and even to be able to sing English songs in good pronunciation. Despite their awareness of theimportance of English and their still low level of English ability, most students were reluctant to learn Englishautonomously.